ECOLOGISTICS, UTILIZATION AND RECYCLING OF VEHICLES: TRENDS AND PROSPECTS - Бойченко, С. В.; Лейда, К.; Іванченко, О. В. (Science-based technologies, 2016)
In the article the appearance of ecological logistics, as a new scientific direction in ecology and economic, its relationship with the problems of utilization and recycling of waste was examined. The improved flowchart of ecologically oriented logistics management was proposed. The problem of transport sector wastes in Ukraine and abroad was studied. Making of wastes and their morphological structure was considered at all stages of the life cycle of the vehicle. The necessity of recycling vehicles that becomes out of service was proved. The ecological problems related to gathering and recycling of vehicles and their components was considered. The significance and feasibility of recycling processes in transport wastes life cycle was proposed and estimated. The complex of measures for gathering and recycling organization of secondary resources motor transport and air transport was considered.